2013
DOI: 10.1111/jpc.12409
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive versus liberal red blood cell transfusion thresholds in very low birth weight infants: A systematic review and meta‐analysis

Abstract: Restrictive RBC transfusion thresholds in VLBW infants may be utilised without incurring clinically important increases in the risk of death or major short-term neonatal morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…In 2014, Ibrahim et al . performed a meta‐analysis which reflects the results of the Cochrane review. These partly contradicting results highlight the need for more studies and clearer evidence to reach global consensus on transfusion thresholds and improve neonatal care .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Ibrahim et al . performed a meta‐analysis which reflects the results of the Cochrane review. These partly contradicting results highlight the need for more studies and clearer evidence to reach global consensus on transfusion thresholds and improve neonatal care .…”
Section: Discussionmentioning
confidence: 99%
“…In the Cochrane systematic review, Whyte and Kirpalani [11] concluded that the use of restrictive as compared to liberal transfusion guidelines resulted in modest reductions in exposure to transfusion, without a significant impact on death or major morbidities. In 2014, Ibrahim et al [24] performed a meta-analysis which reflects the results of the Cochrane review. These partly contradicting results highlight the need for more studies and clearer evidence to reach global consensus on transfusion thresholds and improve neonatal care [2,25].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for limiting TRIM and detrimental proinflammatory effects of RBC transfusions have been investigated, but the use of leukoreduction has given contradictory clinical results . The recent ARIPI study failed to demonstrate improved outcomes from the use of fresh RBCs (≤7 days old) in very low birthweight infants, and a restrictive RBC transfusion policy has not been found to decrease the risk of TANEC . Thus, care and caution in prescribing RBC transfusions following shared guidelines seems to be the most powerful approach to create benefits without detrimental effects from RBC transfusional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with most previously published meta-analyses. [6,8,26,27] However, unlike the latter reports, we pooled data only from randomized trials assessing adult hip or knee surgery patients that compared restrictive and liberal transfusion thresholds. The clinical settings and thresholds for blood transfusion were similar in all the trials included in the current meta-analysis.…”
Section: Discussionmentioning
confidence: 99%